New preparation method of low-temperature sinterable Pb(Mg1/3Nb2/3)O-3 powder and its dielectric properties - Han, KR; Kim, S (KLUWER ACADEMIC PUBL, 2000)
A relaxor ferroelectric material, Pb(Mg1/3Nb2/3)O-3(PMN) with perovskite phase was prepared by one-step calcination in the present study. The PMN powder with > 99% perovskite phase was prepared successfully by adding an aqueous Mg(NO3)(2) solution rather than MgO to the alcoholic slurry of PbO and Nb2O5, followed by calcination at 950 degrees C for 2 h. The DSC and XRD analysis showed that the pathway in the one-step calcination was different from those of the known columbite or solution processes. The PMN powder sintered to 95.6% of the theoretical density at even 900 degrees C for 2 h. Its room temperature dielectric constant showed 13800 at 1 kHz, the loss of dielectric constant of 0.05% and the specific resistivity of 2.4 x 10(10) Ohm . cm. (C) 2000 Kluwer Academic Publishers.
Keywords: LEAD MAGNESIUM NIOBATE; ACTUATORS; CERAMICS; ROUTE; GEL